2012
DOI: 10.1134/s0031918x12020056
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneities of the interface produced by explosive welding

Abstract: Results of studying structure of the transition zone for a number of joints produced by explosive welding are presented. The joints of dissimilar metals (titanium-orthorhombic titanium aluminide, coppertantalum, and others) have been investigated. The welded pairs of metals differ from each other in mutual sol ubility; moreover, some pairs (copper-tantalum) virtually lack it. The interface was found to be uneven; it contains inhomogeneities, irrespective of whether it is flat or wavy. It is shown that the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In the area of wave formation, crystals are elongated in the direction of metal flow. Their shape and size are determined by fragmentation pro cesses [5][6][7][8]. Near the area of plastically deformed metal, the grain size decreases due to recrystallization and twinning.…”
Section: Resultsmentioning
confidence: 99%
“…In the area of wave formation, crystals are elongated in the direction of metal flow. Their shape and size are determined by fragmentation pro cesses [5][6][7][8]. Near the area of plastically deformed metal, the grain size decreases due to recrystallization and twinning.…”
Section: Resultsmentioning
confidence: 99%
“…Below we consider in detail a Cu-Ta system characterized by nearly zero mutual solubility of the components in the solid state [ 9 , 10 ] and high structural stability and mechanical strength of the joint at elevated temperature. Wang et al [ 11 ] note the absence of structural transformations and changes in mechanical properties of a sputter-deposited Cu-Ta composite during heating at 900°C for 100 h. Greenberg et al [ 12 , 13 ] have shown that explosive welding of materials with no mutual solubility results in the formation of a heterophase mixture in the joint region with particle sizes of the dispersed phase similar to those of colloids.…”
Section: Introductionmentioning
confidence: 99%